Autonomous Defense Based on Biogenic Nanoparticle Formation in Daunomycin-Producing Streptomyces - Karel Beneš; Vladislav Čurn; Baveesh Pudhuvai; Jaroslav Motis; Zuzana Michalcová; Andrea Bohatá; Jana Lencová; Jan Bárta; Michael Rost; Andreas Vilcinskas; Vladimír Maťha (Microorganisms)
Daunomycin is a chemotherapeutic agent widely used for the treatment of leukemia, but its toxicity toward healthy dividing cells limits its clinical use and its production by fermentation. Herein, we describe the development of a specialized cultivation medium for daunomycin production, including a shift to oil rather than sugar as the primary carbon source. This achieved an almost threefold increase in daunomycin yields, reaching 5.5–6.0 g/L. Daunomycin produced in the oil-based medium was predominantly found in the solid sediment, whereas that produced in the sugar-based medium was mostly soluble. The oil-based medium thus induces an autonomous daunomycin-resistance mechanism involving biogenic nanoparticle formation. The characterization of the nanoparticles confirmed the incorporation of iron and daunomycin, indicating that this approach has the potential to mitigate cytotoxicity while improving yields. The presence of proteins associated with iron homeostasis and oxidative stress responses revealed the ability of the production strain to adapt to high iron concentrations. Our findings provide insight into the mechanisms of biogenic nanoparticle formation and the optimization of cultivation processes. Further investigation will help to refine microbial production systems for daunomycin and also broaden the application of similar strategies for the synthesis of other therapeutically important compounds.